2023
DOI: 10.1371/journal.pone.0271010
|View full text |Cite
|
Sign up to set email alerts
|

I am a scientist: Overcoming biased assumptions around diversity in science through explicit representation of scientists in lectures

Abstract: The lack of diversity in Science, Technology, Engineering, and Mathematics (STEM) is a significant issue for the sector. Many organisations and educators have identified lack of representation of historically marginalised groups within teaching materials as a potential barrier to students feeling that a Science, Technology, Engineering, and Mathematics (STEM) career is something that they can aspire to. A key barrier to addressing the issue is providing accessible and effective evidence-based approaches for ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…2−5 Even simple interventions such as adapting presentation slides to include full names and photos of scientists, in addition to traditional citations, can make a significant difference to the experience of students from minority groups. 16 It has also been determined that inclusion of diverse perspectives is fundamental to giving a sense of belonging to underrepresented groups. 4 Previous studies have shown the importance of having mentors matched by gender and ethnicity to increase mentorship experience.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2−5 Even simple interventions such as adapting presentation slides to include full names and photos of scientists, in addition to traditional citations, can make a significant difference to the experience of students from minority groups. 16 It has also been determined that inclusion of diverse perspectives is fundamental to giving a sense of belonging to underrepresented groups. 4 Previous studies have shown the importance of having mentors matched by gender and ethnicity to increase mentorship experience.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This approach also advocates elevating the value placed on STEM skills across a wide range of professions. Various initiatives have been launched at different levels, from primary and high schools ,, to universities, to inspire underrepresented groups and show the importance of continuing into these type of career paths, but there is still much to be done to be able to encourage more students from a wider variety of backgrounds. Even simple interventions such as adapting presentation slides to include full names and photos of scientists, in addition to traditional citations, can make a significant difference to the experience of students from minority groups . It has also been determined that inclusion of diverse perspectives is fundamental to giving a sense of belonging to underrepresented groups .…”
Section: Introductionmentioning
confidence: 99%
“…Faculty and scholars, especially in the United States and United Kingdom, are encouraged to diversify their teaching materials, consider more inclusive approaches to content, and incorporate culturally-responsive examples into their courses [1]- [4]. However, little guidance exists on how to go about finding, evaluating, and using research from scholars belonging to underrepresented identities.…”
Section: Introductionmentioning
confidence: 99%